Comprehensive assessment of the safety of olodaterol 5 µg in the Respimat® device for maintenance treatment of COPD: comparison with the long-acting β2-agonist formoterol. (December 2017) - Koch, Andrea; Watz, Henrik; Maleki-Yazdi, M.; Bothner, Ulrich; Tetzlaff, Kay; Voß, Florian; McGarvey, Lorcan
Abstract This analysis provides a comprehensive clinical assessment of the long-term safety of the licensed dose of olodaterol (5 µg once daily [QD] via Respimat® inhaler) in patients with chronic obstructive pulmonary disease by exploring the occurrence of acknowledged side effects of long-acting β2 -agonists as well as those included in the olodaterol and formoterol labels. We analysed pooled data from two replicate, double-blind studies of olodaterol (5 µg QD via Respimat® ) compared to formoterol (12 µg twice daily [BID]) or placebo over 48 weeks (1222.13, NCT00793624; 1222.14, NCT00796653). Patients could continue their background treatment. The analysis considered adverse events (AEs) typically associated with β2 -agonists, including cardiovascular events, as well as administration-related events. Descriptive statistics were provided for the incidence of AEs and aggregated AEs. The analysis included 1379 patients: 460 placebo, 459 olodaterol and 460 formoterol; AEs were reported by 70.9, 71.7 and 69.1% of patients, respectively. Exposure-adjusted incidence rates of cardiac AEs (arrhythmia and myocardial ischaemia) and cough were numerically lower in the olodaterol group than the formoterol group, while nasopharyngitis, throat irritation, metabolism and psychiatric disorders were numerically higher in the olodaterol group. The most frequent event in the olodaterol group was nasopharyngitis (placebo 8.0%; olodaterol 12.9%; formoterol 10.0%). Except for cough (incidence rate ratio of 0.46 [95% confidence interval 0.24, 0.89] in favour of olodaterol), there were no significant differences between active groups. In conclusion, olodaterol 5 µg QD was well tolerated over 48 weeks with a typical β2 -agonist safety profile comparable to formoterol 12 µg BID. Chronic lung disease: Drug safety confirmed The long-term safety of a recently-certified inhaled drug for the treatment of chronic lung disease is verified by scientists in Germany. The management of chronic obstructive pulmonary disease involves inhaled drugs called long-acting β2 agonists (LABAs). The most recently-certified LABA is called olodaterol. Andrea Koch at the Klinikum der Ludwig-Maximilians-Universität in Munich, Germany, and co-workers have clarified the long-term safety of olodaterol during two trials that compared it with formoterol, an existing LABA. The trials lasted 48 weeks and involved 1379 patients—460 were given a placebo, 459 received 5 µg olodaterol via a Respimat device, and 460 received formoterol. Side effects from olodaterol were no more severe or persistent than those associated with formoterol. Reassuringly, the new drug also displayed similar or slightly lower incidence of cardiovascular side effects such as heart palpitations compared with formoterol.